Life satisfaction and air quality in Europe - Susana Ferreira; Alpaslan Akay; Finbarr Brereton; Juncal Cu\~nado; Peter Martinsson; Mirko Moro (Institute for the Study of Labor (IZA), 2012)
Concerns for environmental quality and its impact on people's welfare are fundamental arguments for the adoption of environmental legislation in most countries. In this paper, we analyse the relationship between air quality and subjective well-being in Europe. We use a unique dataset that merges three waves of the European Social Survey with a new dataset on environmental quality including SO2 concentrations and climate in Europe at the regional level. We find a robust negative impact of SO2 concentrations on self-reported life satisfaction.
Keywords: I31; Q51; Q53; Q54; 330; air quality; SO2 concentrations; subjective well-being; life satisfaction; Europe; European Social Survey; GIS; Zufriedenheit; Schwefeldioxid; Luftverunreinigung; Luftreinhaltung; Europa